Yearbook of the European Convention on Human Rights / Annuaire de la Convention Europeenne des Droits de L’Homme - Council of Europe Staff. author. aut Link
XIX, 1173 p.
Keywords: Volume I3 of the Yearbook of the European Convention on Human Rights relates to the year I970 and reflects a return to the usual pattern of activity under the Convention during that year, after the exceptional situation produced in I969 by the "Greek Case". This volume is published somewhat later than usual, because an extra volume in this series has been published between volumes I2 and I3 containing the Report of the European Com mission of Human Rights and the Resolution of the Committee of Ministers of the Council of Europe relating to the "Greek Case". Part I of this Volume contains, as usual, the basic texts, chief among which are the amendments now made to the Convention following the entry into force on 2I September I970 of the Third Protocol, which relates to the procedure of the Commission. On the same date, the Second Protocol also entered into force, conferring on the Court of Human Rights competence to give advisory opinions. The text of this Protocol is to be found in Volume 6 at pages 3ff. The amendments and additions to the Rules of Court consequent upon the entry into force of the Second Protocol are set out in Part I of this Volume.